2022
DOI: 10.3389/fonc.2022.791962
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Pan-Cancer Analysis of 33 Human Cancers Reveals the Potential Clinical Implications and Immunotherapeutic Value of C-X-C Motif Chemokine Ligand 13

Abstract: BackgroundC-X-C Motif Chemokine Ligand 13 (CXCL13) plays a crucial part in the pathogenesis of numerous lymphoproliferative disorders, inflammatory responses, and autoimmune diseases. CXCL13 also influence tumor development and prognosis, and be a potential target for cancer treatment. However, CXCL13 expression-based panoramic picture in pan-cancer remain unclear. This study focused on elucidating different expression levels, prognostic significance, immune-related characteristics, epigenetic variations, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that TMB and MSI levels are critical biomarkers for the immunotherapy efficacy in cancer management [ 18 ]. Therefore, we further investigated the relation of RNF43 expression with MSI and TMB in different cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that TMB and MSI levels are critical biomarkers for the immunotherapy efficacy in cancer management [ 18 ]. Therefore, we further investigated the relation of RNF43 expression with MSI and TMB in different cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Its double-sided role in apoptosis remains to be explored and the mechanisms remain ambiguous. Furthermore, it is essential to acknowledge that CXCL13 might facilitate the onset, progression, and adverse prognosis of cancer by triggering additional oncogenic pathways, like the JAK-STAT pathway, via the chemokine pathway or cytokine receptor pathway (Zhang et al 2022 ). This may be related to the duality of the immune system in tumor progression (Ozga et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1A-K clearly illustrates a signi cant elevation of PDXK expression in tumor tissue compared to normal tissue. Additionally, we examined PDXK expression levels across various human cancers using the TCGA database [27,28]. Notably, tumor tissues of COAD (Colon adenocarcinoma) and READ (Rectum adenocarcinoma) exhibited higher PDXK expression when compared to normal tissues (Fig.…”
Section: Pdxk Is Overexpressed In Crcmentioning
confidence: 99%